2021
DOI: 10.1038/s41598-021-85349-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age-related hearing loss and hearing aid experience on sentence processing

Abstract: Age-related hearing loss typically affects the hearing of high frequencies in older adults. Such hearing loss influences the processing of spoken language, including higher-level processing such as that of complex sentences. Hearing aids may alleviate some of the speech processing disadvantages associated with hearing loss. However, little is known about the relation between hearing loss, hearing aid use, and their effects on higher-level language processes. This neuroimaging (fMRI) study examined these factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…In addition, hearing-impaired patients experience increased recruitment of the CN after hearing aid use (Vogelzang et al, 2021). Cerebellar output is anatomically and functionally connected to the frontal cortex through the subcortical area, forming a cerebrocerebellar circuit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hearing-impaired patients experience increased recruitment of the CN after hearing aid use (Vogelzang et al, 2021). Cerebellar output is anatomically and functionally connected to the frontal cortex through the subcortical area, forming a cerebrocerebellar circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies have also discovered the activation of the cerebellum during auditory input, and auditory deprivation has been found to interfere with communication between CN and other cortical networks ( Brady et al, 2019 ). In addition, hearing-impaired patients experience increased recruitment of the CN after hearing aid use ( Vogelzang et al, 2021 ). Cerebellar output is anatomically and functionally connected to the frontal cortex through the subcortical area, forming a cerebrocerebellar circuit.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with impairment of the precentral gyrus show inability in phonological judgment [ 32 ]; in addition, activation of the precentral gyrus during phonological tasks is well recognized among healthy individuals [ 33 , 34 ]. Moreover, elderly individuals with hearing loss showed activation of several areas, including the precentral gyrus, when encountering complex sentences [ 35 ], suggesting that functional activity of the precentral gyrus is important in language processing when individuals already have impaired language ability. Combining accumulating evidence of the precentral gyrus in phonology and the notion that the frontal-cerebellar circuit is crucial in language processing, we assumed that the cerebrocerebellar circuits of rCrus I-lPreCG and rLobule VI-lPreCG are parts of the phonological network and influence language performance in aphasic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Another important variable that could have a role in modifying the interactions between cognitive and auditory functions is the neuroplasticity derived from the use of hearing aids in subjects with hearing loss. In this line, recent reports show that the use of hearing aid devices can induce neuroplasticity and modify the performance in cognitive tests (Glick and Sharma, 2020;Vogelzang et al, 2021). These recent findings should be considered as an important caveat for future studies, due to the fact that the majority of previous studies on audition and cognition used mixed data from subjects with and without the use of hearing aids (O'Brien et al, 2021), or do not report whether individuals were aided or not with auditory devices such as hearing aids or cochlear implants (Humes et al, 1994(Humes et al, , 2013Sheft et al, 2015;Murphy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%